2015
DOI: 10.5114/ceji.2015.54599
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fingolimod on basic lymphocyte subsets frequencies in the peripheral blood of multiple sclerosis patients – preliminary study

Abstract: BackgroundFingolimod is a drug administered orally to adult patients treated for relapsing remitting course of multiple sclerosis (MS). Mode of action of fingolimod is based on intense S1P1 receptor stimulation and “arresting” lymphocytes in lymphatic organs. Objective of the research was to assess changes in the frequencies of basic lymphocyte subsets in patients treated for multiple sclerosis with the use of fingolimod.Material and methodsStudy group comprised of 25 previously untreated adult patients with M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 34 publications
3
9
0
1
Order By: Relevance
“…We thus examined the direct effects of Fingolimod on T cells populations in vivo, with a focus on cytokine secretion and expression of exhaustion markers. We first confirmed published data demonstrating the decrease in T cell numbers in the circulation of patients under Fingolimod treatment [38,[55][56][57][58][59] and the lack of effects on monocyte and NK cell counts [60].…”
Section: Discussionsupporting
confidence: 85%
“…We thus examined the direct effects of Fingolimod on T cells populations in vivo, with a focus on cytokine secretion and expression of exhaustion markers. We first confirmed published data demonstrating the decrease in T cell numbers in the circulation of patients under Fingolimod treatment [38,[55][56][57][58][59] and the lack of effects on monocyte and NK cell counts [60].…”
Section: Discussionsupporting
confidence: 85%
“…[40][41][42] In this 12M follow-up study, we determined the effect of Fingolimod on the frequency of different cytokine-producing CD4+ and CD8+ T cell subsets. Consistent with other studies, 29,40,43 we also found decreased percentages of both CD4+ and CD8+ T lymphocytes in the peripheral blood of MS patients with a predominant reduction in the CD4+ T cells.…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless, in the context of a possible clinical trial of the gefitinib-FTY720 combination in breast cancer patients, we investigated whether a FTY720 dose with antitumor efficacy in mice (in combination with gefitinib) would compromise the immune system. FTY720 inhibits T cell mobilization from lymphoid tissues [ 20 ], which in some patients can result in lymphopenia [ 32 , 47 ]. If this depletes tumor-resident lymphocytes it could potentially be deleterious to breast cancer patients undergoing therapy, since a high tumor-associated lymphocyte count is a positive predictor of treatment response [ 48 ].…”
Section: Discussionmentioning
confidence: 99%